Legal Basis for a National Space Legislation - Hermida, Julian; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2004)
A. GENERAL BACKGROUND (3z(BThe foremost goal of the international community in the area [of private space launch services] should be to induce states to implement effective licensing procedures applicable to commercial ventures for which state responsibility may 1 exist. (3y (B1. PRIVATE SECTOR PARTICIPATION IN THE SPACE INDUSTRY In the first decades of the space age, military and state security motivations indicated the direction of national space programs. Now the development of space activities depends essentially upon the possibility of recovering 2 investments. Private sector-driven commercial endeavors in outer space have been increasing exponentially and have experienced a significant quantitative growth over the last years. Spacefarers promote commercial participation of private companies in operations related to outer space, and, thus, the private sector is now increasingly providing satellite telecommunications, remote sensing, global positioning and space launch services directly to its customers. In this context, overall revenues for the worldwide space industry 3 amounted to US$ 82 billion in 2001. In the late 1990$1 (Bs the transponder demand, in particular Ku- band transponders, was consistently on the rise due 4 to the escalated utilization of geostationary satellite transponders. Global positioning systems have been playing an increasingly important role in navigation, and remote sensing systems are mapping and documenting nearly 1 E. A. Frankle & E. J. Steptoe, (3z(BLegal Considerations Affecting Commercial Space Launches From International Territory(3y(B, (1999) 50 IISL at 10. Emphasis added. 2 H. L.s
Introduction -- I: The International Legal Framework. A. International Responsibility and Reliability. B. Authorization and Supervision. C. Registration. D. Conclusions -- II: The National Legal Framework. A. United States of America. B. Russian Federation. C. Australia. D. United Kingdom. E. Ukraine. F. Sweden. G. South Africa. H. Japan. I. France. J. Canada. K. Harmonization and New Rules. L. Conclusions -- III: Argentine Space Law and Policy. A. National Application of International Law. B. Nature of Argentine National Space Law. C. Responsibility and Liability. D. Implementation of the Authorization and Supervision Principle. E. Implementation of the Registration Obligations. F. Conclusions -- IV: Conclusions and Proposal. A. Conclusions Regarding the International Legal Framework. B. Conclusions Regarding the National Legal Framework. C. Conclusions Regarding Argentine Space Law and Policy. D. Recommendations and Proposal -- About the Author -- Bibliography -- List of Acronyms.
Keywords: Observations, Astronomical; Astronomy$1 (BObservations.s; Law of the sea; International law; Private international law; Conflict of laws; Criminology; Astronomy, Observations and Techniques; Law of the Sea, Air and Outer Space; Private International Law, International & Foreign Law, Comparative Law .; Criminology and Criminal Justice, general